Analyzing the Efficiency of the Curly Red Chili (Capsicum annuum L.) Supply Chain: A Structure-Conduct-Performance Approach in East Payakumbuh Subdistrict - Fariz Fahrezi Taufiq; Syarif Imam Hidayat; Ika Sari Tondang (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
Curly red chili (Capsicum annuum L.) is a strategic horticultural commodity in Indonesia, vital for both food security and rural livelihoods. In East Payakumbuh Subdistrict, West Sumatra, it serves as a primary income source for local farmers. However, the supply chain faces significant challenges, including price volatility, constrained market access, and a high dependence on intermediaries, which collectively erode farmer bargaining power. Applying the Structure-Conduct-Performance (SCP) framework, this study analyzes the market dynamics of curly chili. We collected primary data through in-depth interviews with key supply chain actors farmers, collectors, wholesalers, retailers, and sub-terminal agricultural officers using snowball sampling. Our quantitative analysis employs concentration ratios (CR4), Minimum Efficiency Scale (MES), marketing margins, and farmer’s share to evaluate market efficiency. The findings reveal an oligopsonistic market structure, where four dominant firms control 95.48% of purchases, supported by a high MES of 85.82%. This concentration, coupled with farmers' reliance on these few buyers, results in persistently low farmer bargaining power. Furthermore, marketing channel efficiency is heterogeneous; one distinct channel demonstrates superior efficiency and returns a higher profit share to farmers. These results underscore the imperative for policy measures designed to strengthen farmer cooperatives, reform trading mechanisms, and facilitate direct market linkages to enhance overall supply chain equity and performance.